Pengaruh Kompensasi, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Studi Pada Dinas Kepemudaan Olahraga Kebudayaan Pariwisata dan BPPDK Tasikmalaya - Ulfa Hafsari Rachmi; Muis Wirasujatma; Widia Sofyan, Verra Rosyallia (POLITEKNIK LP3I, 2023)
The purpose of this study was to determine the effect of Simultaneous and Partial between Preventive Maintenance and Breakdown Maintenance on the Smooth Production Process of a case study at the Marrivosa Rubber Sandal Cigantang company, Tasikmalaya city. The research method used is survey and quantitative methods. The sample used is random sampling. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 16. The results showed that simultaneously Preventive Maintenance and Breakdown Maintenance had a significant effect on the Smoothness of the Production Process. Partially Preventive Maintenance has a significant effect on the Smoothness of the Production Process. Partially Breakdown Maintenance has a significant effect on the Smoothness of the Production Process